Dakwah Lingkungan Perspektif Al-Qur’an - Muhyiddin, Asep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
Daâ€™wah have tight catch with various etnics, one of them called the environment problem. This entity can be parameter ifÂ daâ€™wah activity can give contribution to solute environmental problems. These problems can examine the exsistence of daâ€™wah truth. Al-Qurâ€™an as the holybook of daâ€™wah have viewÂ that the nature is not enemy that has to subjected and submitted, but integrated with human religious world. Al- Qurâ€™ an give moral command that related by this assignment of daâ€™wah practicioner. One-in order to man be active practicioner in managing the environment. Two-in order to man not doing damage to environment. Three- in order to man be friendly to environment.